Pengalaman Perawat Dalam Mengimplementasikan Strategi Pelaksanaan (SP) Tindakan Keperawatan Pada Pasien Halusinasi di Rumah Sakit Jiwa Daerah Surakarta - Sulahyuningsih, Evie, Arum Pratiwi, S.Kep., M.Kes (Kep), Sahuri Teguh, S.Kep., Ns (2016)
One of standard operational procedure (SOP) used to handle patient with mental disturbance are use nursing implementation strategy (IS), the implemented nursing at mental disorder patient. The implementing strategies (IS) are implementing standards model technical approach for mental disturbance client that aimed hallucination as mayor sign. This time at mental hospital district Surakarta, when give a nursing care in client was use nursing implementation strategy (IS) in client with hallucination.The goal for this research is to knows the nurse experience when they are implementing strategy nurse(IS) at client with hallucination. This research are use qualitative method with phenomenology approach. Total participant are 11 person who they are nursing in ward hospitalization at Mental Hospital District Surakarta. To selected participant are helped by the head nurse station and match with reseacer criteria and when till redundancy or data has been saturated, than the participant are not gift a new information. Data are collected with through interview and observation on nurse that implemented strategy nurse (IS) on patient with hallucination.The research result after the process of analytic thematic, there are identified eight topic, that is : to care patient patient need a knowledge and technical approach, ineffectiveness application of implementation Strategy (IS) in acute space, un matching in documentation with implementation Strategy (IS), implementation Strategy (IS) has a functioning to standard implementation a nurse, misperception a nurse that the result of the nursing implementation strategy (IS), the weakness nursing implementation strategy (IS) on patient with hallucination, the un matching between the treatment strategy in family with in patient of hallucination, strange behavior (bizarre) of the patient against the response of implementation Strategy (IS).To next researcher, a research of the result implemented strategy are very limited, than I hope to continued nurse research to increase of the mental nursing care.